2014
DOI: 10.1002/ece3.1286
|View full text |Cite
|
Sign up to set email alerts
|

Preadaptation and post‐introduction evolution facilitate the invasion ofPhragmites australisin North America

Abstract: Compared with non-invasive species, invasive plant species may benefit from certain advantageous traits, for example, higher photosynthesis capacity and resource/energy-use efficiency. These traits can be preadapted prior to introduction, but can also be acquired through evolution following introduction to the new range. Disentangling the origins of these advantageous traits is a fundamental and emerging question in invasion ecology. We conducted a multiple comparative experiment under identical environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 65 publications
4
36
0
Order By: Relevance
“…Given that the climate in the introduced range was more advantageous than that in the original range for the survival of common reed because of abundant precipitation and warm temperature, the introduced environment did not provide enough selection pressures to shape the stable genetic and epigenetic structure of introduced populations. Therefore, we cannot ignore the potential effect of preadaptation and ecological fitting based on the inherently high phenotypic plasticity during the invasion process of common reed (Guo, Lambertini, Nguyen, Li, & Brix, 2014; Guo et al., 2016), which may be correlated with plastic epigenetic mechanisms (Gao et al., 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Given that the climate in the introduced range was more advantageous than that in the original range for the survival of common reed because of abundant precipitation and warm temperature, the introduced environment did not provide enough selection pressures to shape the stable genetic and epigenetic structure of introduced populations. Therefore, we cannot ignore the potential effect of preadaptation and ecological fitting based on the inherently high phenotypic plasticity during the invasion process of common reed (Guo, Lambertini, Nguyen, Li, & Brix, 2014; Guo et al., 2016), which may be correlated with plastic epigenetic mechanisms (Gao et al., 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Guo et al. () found that photosynthesis‐ and growth‐related traits of the invasive North American populations became different from the ancestral European populations, possibly as a response to the new niche (Guo et al., ). We cannot, however, discount the possibility that the differences that we observed could also be due to introductions of different populations from Europe originating from a variety of environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…() and Lambertini, Sorrell, Riis, Olesen, and Brix () documented genetic differentiation between the introduced North American and native European populations, and with common garden experiments, Guo et al. () revealed that post‐introduction evolution occurred with the invasion, and Pyšek et al. () identified the differences in genome size as a key trait associated with invasiveness of the common reed populations.…”
Section: Introductionmentioning
confidence: 99%
“…berlandieri haplotype (Saltonstall 2002) have been found in North America. When nuclear markers and the global phylogeography of the genus are considered, introduced haplotype M has two populations in North America: one genetically similar to the European population from which it is assumed to have descended, and one different, presumably due to postintroduction evolution that occurred in the introduced range (Lambertini et al 2012b;Guo et al 2014). The divergent population is predominantly established along the East Coast (the Atlantic Coast cluster in Lambertini et al 2006Lambertini et al , 2012b, in areas where the invasion has been extremely aggressive and the native P. australis ssp.…”
Section: Introductionmentioning
confidence: 99%